Molecular signature of coronary stent thrombosis: oxidative stress and innate immunity cells - Cubedo, Judit; Blasco, Ana; Padró, Teresa; Ramaiola, Ilaria; Juan-Babot, Oriol; Goicolea, Javier; Fernández-Díaz, José Antonio; Oteo, Juan Francisco; Badimon, Lina (Thrombosis and Haemostasis, 2017)
The clinical impact of in-stent thrombosis is high because it is associated with high mortality and 20 % of the patients suffer a recurrent event within the two following years. The aim of this study was to characterise the morphologic and proteomic profile of in-stent thrombi (IST) in comparison to thrombi developed on native coronary arteries (CT) to identify a differential molecular signature. The study included 45 patients with ST-elevation-myocardial-infarction (STEMI) treated by primary-percutaneous-intervention and thrombus aspiration: 21 had IST and 24 had CT. Thrombi were characterised by morphologic immunohistochemical analysis and differential proteomic profiling (2-DE+MALDI-TOF/TOF). Bioinformatic analysis revealed differences in proteins related to oxidative-stress and cell death/survival. IST showed a higher content of structural proteins (gelsolin, actin-cytoplasmic-1, tropomyosin, and myosin) together with an imbalance in redox-homeostasis related proteins (increased superoxide-dismutase and decreased peroxiredoxin-2 thrombus content), and a coordinated increase of chaperones (HSP60 and HSC70) and cellular quality control-related proteins (26S–protease-regulatory-subunit-7). These changes were reflected into a significant decrease in HSC70 systemic levels and a significant increase in advanced-oxidation-protein-products (AOPP) indicative of increased oxidative stress-mediated protein damage in IST. Our results reveal an imbalance in redox-related proteins indicative of an exacerbated oxidative-stress that leads to an accumulation of AOPP serum levels in IST. Moreover, the coordinated increase in chaperones and regulatory proteins reflects the activation of intracellular protection mechanisms to maintain protein integrity in IST. The failure to counterbalance the stress situation could trigger cellular apoptosis leading to the destabilization of the thrombus and to a worse prognosis of IST-STEMI-patients.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Acute myocardial infarction; thrombus; in-stent thrombosis; oxidative stress; chaperones